Fungal Cultivars of Higher Attine Ants Promote Escovopsis Chemotropism - de Oliveira, Karina B. [UNESP]; Goes, Aryel C. [UNESP]; Silva, Airton D.; Vieira, Paulo C.; Rodrigues, Andre [UNESP] (Springer Nature, 2024)
In varied environments, microorganisms search for partners or nutritional resources using chemical signals. Microbes are drawn (chemotaxis) or grow directionally (chemotropism) towards the chemical source, enabling them to establish and maintain symbiosis. The hypocrealean fungi Escovopsis enhance their growth towards the basidiomycete fungus Leucoagaricus gongylophorus, which is cultivated by leaf-cutting attine ants for food. Although directional growth is well documented in this symbiosis, it is unclear whether non-volatile or volatile organic compounds participate in the interaction between cultivar and Escovopsis, and which specific chemical compounds might attract and induce chemotropism. In this study, we examined the growth responses of Escovopsis isolates to non-volatile and volatile organic compounds produced by fungal cultivars of higher attine ants. We also isolated and identified molecules released by the ant-cultivar and assessed the chemotropism of Escovopsis towards them. Our results indicate that the growth of Escovopsis is stimulated in the presence of both non-volatile and volatile compounds from fungal cultivars. We also identified three isomeric diketopiperazines molecules from crude extracts of the ant cultivar, suggesting that these might play a role in Escovopsis chemotropism. Our findings provide insights into the complex chemical interactions that govern the association between Escovopsis and fungal cultivars.